The Impact and Reshaping of Traditional Music Production Models by the Rise of Independent Musicians (Journal of humanities and social sciences exploratio, 2026)
Over the past decade, the widespread adoption of digital audio workstations, streaming platforms, and short video media has significantly transformed the organizational methods and power structures of music production. Unlike the traditional model centered on record companies, which relies on upfront capital investment and specialized labor division, independent musicians have gained greater autonomy in creation, production, distribution, and dissemination through low-cost digital tools and platform-based distribution mechanisms.  This study, based on literature review and case analysis, examines the impact of the rise of independent musicians on traditional music production from four dimensions: production entities, resource allocation, dissemination mechanisms, and value evaluation. The research suggests that the emergence of independent musicians has not ended industrialized music production but has instead shifted the control of production rights from institutional monopolies to a redistributed model involving creators, platforms, and professional organizations. Meanwhile, record companies have gradually transitioned from upfront controllers to post-production resource integrators.  Additionally, platform algorithms and traffic rules have formed a new intermediary structure. Consequently, the contemporary music industry is evolving into a hybrid production ecosystem characterized by "individual initiation—platform validation—industrial continuation."
Keywords: Independent musicians; Music production models; Digital media; Platformization; Industrial transformation